Intramural florid cystic endosalpingiosis of the uterus after menopause - Hattori, Yui; Sentani, Kazuhiro; Matsuoka, Naoki; Nakayama, Hirofumi; Hattori, Takuya; Kudo, Yoshiki; Yasui, Wataru (Polish Journal of Pathology, 2018)
Endosalpingiosis is a benign condition characterized by the presence of tubal epithelium outside the fallopian tube and the absence of endometrial stroma. Florid cystic endosalpingiosis is a very rare form of endosalpingiosis that presents as a tumor-like lesion. We report the case of a 67-year-old woman who presented with a cystic lesion of the uterus. Macroscopically, a cut section revealed a multicystic, whitish mass in the myometrium of the fundus. Histologically, the lesion consisted of numerous variably sized glands that were lined with a single or stratified layer of ciliated columnar cells similar to tubal epithelium.